Data on the abundance of tick maintenance hosts and their predators - Jaenson, Thomas G.T. (Uppsala University, 2017)
Data comparing hunting data of the major tick maintenance hosts and two of their important predators, and four climatic variables with the annual numbers of human cases of neuroinvasive TBE. Data for six Swedish regions where human TBE incidence is high or has recently increased are examined by a time-series analysis. Results from the six regions are combined using a meta-analytical method.

Ticks were collected from resident and migratory birds captured at the Ottenby Bird Observatory, Öland, Sweden, from March to November 2009. Ticks were molecularly identified to species, and morphologically to developmental stage, and the presence of Borrelia bacteria and TBEV was determined by quantitative real-time PCR.

See more information about data and data collection in "The importance of wildlife in the ecology and epidemiology of the TBE virus in Sweden: incidence of human TBE correlates with abundance of deer and hares" by Jaenson et al (2018)


Description of the four datafiles:

Culling:
Data collector: Svenska Jägareförbundet, Öster Malma, 611 91 Nyköping, Sverige
Data curator: Thomas Jaenson & Erik Petersson
Data manager: Thomas Jaenson & Erik Petersson
Numbers of Fallow deer, Roe deer, Mountain hare, Red deer, Wild boar, Elk, European hare, Eurasian lynx and Red fox killed in Stockholm county, Uppsala county, Södermansland county, Östergötland county, Skåne county and Västra Götaland county 1960-2011


Vegetation period:
Data collector: Sveriges Meteorologiska och Hydrologiska Institut, 603 80 Norrköping, Sverige
Data curator: Thomas Jaenson & Erik Petersson
Data manager: Thomas Jaenson & Erik Petersson
Vegetation period defined as number of days per year having a daily mean temperature equal to or above 5°C
Sites: Såtenäs, Gotska Sandön, Bromma, Göteborg Säve
Years: 1961-2012


Temperature:
Data collector: Sveriges Meteorologiska och Hydrologiska Institut, 603 80 Norrköping, Sverige
Data curator: Thomas Jaenson & Erik Petersson
Data manager: Thomas Jaenson & Erik Petersson

The base for thses data are records of temperatures at four sites in Sweden. Temperture was recorddes every third hour during the period 1 Jan 1961 to 31 July 2012.
Time of day for the tempature records were 00 UTC, 03 UTC, 06 UTC, 09 UTC, 12 UTC, 15 UTC, 18 UTC, 21 UTC.

When records were missing manual interpolations have been done in order to make the seis complete.
In a few instances temperature records have been missing for longer periods (more than one day); in those cases a meso-scaling method have been used to estimate values.

For Gothenburg (Göteborg) records for Säve Airport been used. During the latest years data are lacking for Säve Airport. In order to achive data for Säve:
Values for central Gotherburg were reduce with the values in "Correction Gbg to Säve".
The reducion values are based on daily mean temperatures for central Gothenburg and Säve airport during the years when records were noted at both sites
The reduction was made before rounding off (see below).
All temperature records were rounded off to nearest centigrade; example: records 9.5 - 10.4 °C were rounded off to 10 °C
Thereafter a "temperature surplus" was calculated by subtracing the actual temperature record with 9°C

If the rounded off value was ≤9 the temperature surplus was set to 0 (zero)
Thus a single temperature record of 10°C gives a temperature surplus of 1 and 15°C gives a surplus of 6.
All these tempetaure surplus were added by month, giving monthly temperature sum.
The monthly sums were divided with number of days in the month.
The value resulted from this is "index" in the "Data" table.
All monthly sums have also been added in order to estimate a yearly sum.


TBE-cases 1986-2011:
Data collector: Folkhälsomyndigheten, 171 82 Solna, Sverige & SCB (Statistics Sweden), Box 24300, SE-104 51 STOCKHOLM
Data curator: Thomas Jaenson & Erik Petersson
Data manager: Thomas Jaenson & Erik Petersson

Number of TBE-cases per 100000 inhabitants in Stockholm county, Uppsala county, Södermansland county, Östergötland county, Skåne county and Västra Götaland county 1986-2011.


The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för information om datainsamling och -filer.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data on the abundance of tick maintenance hosts and their predators
Data for article "The importance of wildlife in the ecology and epidemiology of the TBE virus in Sweden: incidence of human TBE correlates with abundance of deer and hares"
Keywords: encephalitis; hjärninflammation; tick-borne encephalitis; fästingburen hjärninflammation; epidemiology; epidemiologi; Biological Sciences; Biologi